2004
DOI: 10.1007/bf02980098
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticonvulsant Evaluations ofN-Cbz-α-amino-N-alkoxyglutarimides

Abstract: In our previous studies for the development of new anticonvulsant of broad spectrum, we found that N-cbz-alpha-aminoglutarimides showed significant anticonvulsant activities of broad spectrum enough to be recommended for the new anticonvulsants and their anticonvulsant activities were dependent on their imide substituent groups. Based on these results, various N-cbz-alpha-amino-N-alkoxyglutarimides, where the imide N-H was substituted with the hydroxy and alkoxy group, were prepared and evaluated for their ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…(Byun et al, 2006;Jung et al, 1998;Kim et al, 2004;Lee et al, 1997Lee et al, , 1999Son et al, 1998) Some of them showed comparable anticonvulsant activities in both of the MES and PTZ tests enough to be recommended as broad spectrum anticonvulsant drug candidates. Kim et al, 2004;Lee et al, 1997Lee et al, , 1999 As seen in Fig. 1, these compounds have either a 5-or a 6-membered α-amino cyclic imide moiety and N-CO-C-N group in their structures.…”
Section: Introductionmentioning
confidence: 96%
“…(Byun et al, 2006;Jung et al, 1998;Kim et al, 2004;Lee et al, 1997Lee et al, , 1999Son et al, 1998) Some of them showed comparable anticonvulsant activities in both of the MES and PTZ tests enough to be recommended as broad spectrum anticonvulsant drug candidates. Kim et al, 2004;Lee et al, 1997Lee et al, , 1999 As seen in Fig. 1, these compounds have either a 5-or a 6-membered α-amino cyclic imide moiety and N-CO-C-N group in their structures.…”
Section: Introductionmentioning
confidence: 96%
“…We previously identified a family of novel anticonvulsants, the N-Cbz-α-aminoglutarimidooxy carboxylate derivatives (Byun et al, 2006;Jung et al, 1998;Kim et al, 2004;Lee et al, 1997;Lee et al, 1999;Son et al, 1998) These compounds can affect the central nervous system (CNS) and have a cyclic imide group (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%